Modulators of hypothalamic-pituitary-gonadal axis for the control of spermatogenesis and sperm quality in vertebrates - Rosaria Meccariello (Frontiers Research Topics, 2014)
Spermatogenesis is a process highly conserved throughout vertebrate species and is mainly under hypothalamic-pituitary control. It occurs in the testis in a stepwise fashion so that committed spermatogonia develop into spermatocytes and enter meiosis to produce round spermatids. These undergo a morphological transformation (spermiogenesis) into mature spermatids (i.e.: spermatozoa), which are differentially released from Sertoli cells (spermiation) depending on the species. In mammals, further transformations are necessary to form mature spermatozoa, suitable for fertilization. Gonadotropins, mainly responsive to gonadotropin-releasing hormone, control spermatogenesis through specific receptors located at the gonadal level. However, besides the endocrine route, the chemical mediators may also act locally in the gonad. Indeed, it is documented that testis physiology, including steroidogenesis and spermatogenesis, does not fully account for traditional endocrine control but an intragonadal network of autocrine and/or paracrine regulators also exists, whose activity, via cell-to-cell communication, regulates germ cell progression and development of qualitatively mature spermatozoa. Of note, a number of testicular modulators, such as gonadotropin releasing hormone, Kiss-peptin, endocannabinoids, has been early isolated in the brain and latest in the gonads. To fully understand precise mechanisms underlying the functional interaction of this intricate network, needless to say, it is crucially required to have detailed information about modulators and target cells. Through synergy between the respective specializations of all the authors, this topic reviewed emerging knowledge about neuroendocrine and local mediators controlling germ cell progression and maturation.